Educational Activities of Preschool Educational Institutions of New Type: Self-Realization of the Child - Olha Domanova (Pedagogical Discourse, 2012)
The article analyzes the experience of educational activities of private preschool educational institutions of new type in Mariupol. Peculiarities of content and form in the organization of each institution with the primary purpose to provide the conditions for children’s self- realization are studied.